2000
DOI: 10.1084/jem.191.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Deleterious Mutations in the Iκbα Gene in the Malignant Cells in Hodgkin's Lymphoma

Abstract: Members of the nuclear factor (NF)-κB family of transcription factors play a crucial role in cellular activation, immune responses, and oncogenesis. In most cells, they are kept inactive in the cytosol by complex formation with members of the inhibitor of NF-κB (IκB) family, whose degradation activates NF-κB in response to diverse stimuli. In Hodgkin's lymphoma (HL), high constitutive nuclear activity of NF-κB is characteristic of the malignant Hodgkin and Reed-Sternberg (H/RS) cells, which occur at low number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
182
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(188 citation statements)
references
References 26 publications
2
182
1
3
Order By: Relevance
“…Constitutive (NF)-B activity is likely to be involved in apoptosis resistance, because (NF)-B activates genes involved in apoptosis resistance, cell activation and proliferation, as well as cytokines and chemokines involved in immunosuppression. 11,12 In summary, our results show that a TP53 gene mutation can be an early transforming event, likely to be important in the resistance to apoptosis of the RS precursors. However, even after the enrichment for RS cells and the use of a highly sensitive mutation detection technique we found TP53 gene mutations in only 3 of 26 (11.5%) HL-involved tissue samples.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Constitutive (NF)-B activity is likely to be involved in apoptosis resistance, because (NF)-B activates genes involved in apoptosis resistance, cell activation and proliferation, as well as cytokines and chemokines involved in immunosuppression. 11,12 In summary, our results show that a TP53 gene mutation can be an early transforming event, likely to be important in the resistance to apoptosis of the RS precursors. However, even after the enrichment for RS cells and the use of a highly sensitive mutation detection technique we found TP53 gene mutations in only 3 of 26 (11.5%) HL-involved tissue samples.…”
Section: Discussionmentioning
confidence: 68%
“…14,15,34 Because of the low incidence of TP53 mutations in HL and the finding that TP53 gene mutations are not restricted to EBVnegative cases, other important steps in the resistance of RS precursors to apoptosis have to be considered. One alternative is based on a recent study 11 in which mutations in the I B␣ gene were found in 2 of 3 EBV-negative cases and no mutations were found in 2 EBV-positive cases. Mutations of the I B␣ protein, which normally functions as the inhibitor of (NF)-B protein, leads to increased levels of (NF)-B protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several of these HL cells and perhaps as many as 10% of HL HRS cell biopsy samples, the lack of IkBa is due to loss-of-function mutations (e.g., small insertions, deletions or nonsense) in one allele of the IKBA gene couples with the deletion or inactivation of the second IKBA allele (Wood et al, 1998;Cabannes et al, 1999;Jungnickel et al, 2000;Emmerich et al, , 2003. As a consequence of the constitutive NF-kB signaling, several NF-kB target genes are overexpressed in HL cells, including ones encoding antiapoptotic proteins (such as A1, c-IAP2, TRAF1 and Bcl-X L ) and growth-promoting proteins (including cyclin D2, CD86 and CD40) (Hinz et al, 2001).…”
Section: Multiple Familial Trichoepitheliomamentioning
confidence: 99%
“…The constitutive NF-kB activity seen in most haematological disorders occurs through several mechanisms, including the chromosomal translocation and subsequent overexpression of BCL-3 in a subset of human B-cell chronic lymphotic leukaemias (McKeithan et al, 1987) and mutations of the IkBa gene that impair its inhibitory function in some cases of Hodgkin's lymphomas (Cabannes et al, 1999;Emmerich et al, 1999;Jungnickel et al, 2000). Gene amplification of NIK or loss of function mutations for inhibitory signalling molecules such as TRAF3 and CYLD have been reported in multiple myelomas (Annunziata et al, 2007;Keats et al, 2007).…”
Section: Introductionmentioning
confidence: 99%